Medical coding - Grebner, Leah A. (McGraw-Hill, 2013)
Medical Coding: Understanding ICD-10-CM and ICD-10-PCS is a comprehensive walkthrough of the new ICD-10-CM and ICD-10-PCS coding systems for coders in every part of healthcare. It covers the fundamentals of medical coding, billing, and documentation, essential to understanding the importance of code selection. In-depth chapters on body systems, signs and symptoms, injuries, and health status provide the full picture of diagnosis coding, preparing coders for ICD-10's new guidelines, terminology, and sequencing. Chapters on the brand-new format of ICD-10-PCS have you covered for the evolution in hospital coding